1995
DOI: 10.1111/j.1600-0714.1995.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of oral submucous fibrosis with special reference to the role of areca nut chewing

Abstract: Oral submucous fibrosis (OSF) is a high risk precancerous condition, predominantly affecting Indians. Consumption of chilli was hypothesized as an etiologic factor on the basis of ecological observations and a solitary animal experimental study. Subsequent epidemiologic studies that included case-series reports, large cross-sectional surveys, case-control studies, cohort and intervention studies have identified areca nut as the major etiologic agent. Tissue-culture studies involving human fibroblasts, areca nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
172
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(173 citation statements)
references
References 35 publications
1
172
0
Order By: Relevance
“…Majority of the users underestimate the potency of the products and believe that as long as they do not swallow it they are protected from its harmful effects hence most of them spit it out. A study showed that 85% of oral lesions were located in the primary area of SLT placement, regardless of fact that it was spit or swallowed (Murti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the users underestimate the potency of the products and believe that as long as they do not swallow it they are protected from its harmful effects hence most of them spit it out. A study showed that 85% of oral lesions were located in the primary area of SLT placement, regardless of fact that it was spit or swallowed (Murti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the situation with an older population in which betel-quid was the most prevalent habit. 2,3,13 Because of the association between the use of areca nut alone and OSF 6,9,11,12 it is possible that by the time the children are entering their teens they already have an increased likelihood of developing OSF. Indeed in India the incidence of OSF amongst children has already been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The age-old adage -"Prevention is better than cure" still holds true in the contemporary world. Therefore, detection of pre-cancers and preventing them on time seems to be the best available tool in the fight against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detection of pre-cancers and preventing them on time seems to be the best available tool in the fight against cancer. [1] Oral submucous fibrosis (OSMF) is a well-recognized potentially malignant condition of the oral cavity. Trace elements have been critically examined in etiology of various diseases, especially cancer.…”
Section: Introductionmentioning
confidence: 99%